Chagas' disease: IgA, IgM and IgG antibodies to T. cruzi amastigote, trypomastigote and epimastigote antigens in acute and in different chronic forms of the disease Doença de Chagas: anticorpos IgG, IgM e IgA contra antígenos de amastigota, tripomastigota e epimastigota de T. cruzi em formas agudas e em diferentes formas crônicas da doença - Kátia S. C. Primavera; Eufrosina S. Umezawa; Benedito Anselmo Peres; Mário E. Camargo; Sumie Hoshino-Shimuzu (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
In an attempt to find a better T. cruzi antigen and possible immunological markers for the diagnosis of different clinical forms of Chagas' disease, amastigote and trypomastigote antigens obtained from immunosuppressed mice infected with T. cruzi (Y strain) were assessed in comparison with conventional epimastigote antigens. A total of 506 serum samples from patients with acute and with chronic (indeterminate, cardiac and digestive) forms, from nonchagasic infections, and from healthy individuals were assayed in immunofluorescence (IF) tests, to search for IgG, IgM and IgA antibodies. Amastigote proved to be the most convenient antigen for our purposes, providing higher relative efficiency indexes of 0.946, 0.871 and 0.914 for IgG, IgM and IgA IF tests, respectively. Anti-amastigote antibodies presented higher geometric mean titers (GMT) than anti-trypomastigote and anti-epimastigote. Anti-amastigote IgG antibodies were found in all forms of Chagas' disease, and predominantly IgA antibodies, in chronic digestive and in acute forms, as well as IgM antibodies, in latter forms. Thus, tests with amastigote antigen could be helpful for screening chagasic infections in blood banks. Practical and economical aspects in obtaining amastigotes as here described speak in favour of its use in developing countries, since those from other sources require more complex system of substruction, specialized personnel or equipment. Com o intúito de se aperfeiçoar o diagnóstico sorológico das diferentes formas clínicas da doença de Chagas, foram estudados antígenos de formas amastigota e tripomastigota, obtidas de camundongos imunossuprimidos infectados com cepa Y de T. cruzi, em comparação com o de epimastigota convencionalmente utilizado. Um total de 506 amostras de soro de pacientes chagásicos com formas aguda e crônicas (indeterminada, cardíaca e digestiva), de indivíduos com infecções não relacionadas e de indivíduos sadios foi analisado por reação de imunofluorescência, para detecção de anticorpos IgG, IgM e IgA. O antígeno de ...